Hypoglycemia in the hospital - Mansur Shomali, Md (Greater Baltimore Medical Center, 2011)
Hypoglycemia is a common adverse event affecting hospitalized patients with diabetes. This paper reviews the data regarding optimization of glucose in hospitalized patients, discusses the scope and significance of hypoglycemia in the hospital, and makes recommendations on how to reduce the risk of this serious adverse event.